Evidence for the evolutionary origin of human chromosome 21 from comparative gene mapping in the cow and mouse. - Threadgill, D S (1991)
To determine the extent of conservation between bovine syntenic group U10, human chromosome 21 (HSA 21), and mouse chromosome 16 (MMU 16), 11 genes were physically mapped by segregation analysis in a bovine-hamster hybrid somatic cell panel. The genes chosen for study span MMU 16 and represent virtually the entire q arm of HSA 21. Because the somatostatin gene (SST), an HSA 3/MMU 16 locus, was previously shown to be in U10, the transferrin gene (TF), an HSA 3/MMU 9 marker, was also mapped to determine whether U10 contains any HSA 3 genes not represented on MMU 16. With the exception of the protamine gene PRM1 (HSA 16/MMU 16), all of the genes studied were syntenic on bovine U10. Thus, all homologous loci from HSA 21 that have been studied in the cow are on a single chromosome. The bovine homolog of HSA 21 also carries several HSA 3 genes, two of which have homologous loci on MMU 16. The syntenic association of genes from the q arm of HSA 3 with HSA 21 genes in two mammalian species, the mouse and the cow, indicates that HSA 21 may have that contained genes now residing on HSA 3. Additionally, the syntenic association of TF with SST in the cow permits the prediction that the rhodopsin gene (RHO) is proximal to TF on HSA 3q.